2011
DOI: 10.1128/iai.00850-10
|View full text |Cite
|
Sign up to set email alerts
|

Full Virulence of Pseudomonas aeruginosa Requires OprF

Abstract: OprF is a general outer membrane porin of Pseudomonas aeruginosa, a well-known human opportunistic pathogen associated with severe hospital-acquired sepsis and chronic lung infections of cystic fibrosis patients. A multiphenotypic approach, based on the comparative study of a wild-type strain of P. aeruginosa, its isogenic oprF mutant, and an oprF-complemented strain, showed that OprF is required for P. aeruginosa virulence. The absence of OprF results in impaired adhesion to animal cells, secretion of ExoT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(169 citation statements)
references
References 76 publications
5
154
2
1
Order By: Relevance
“…4B and C). Recent evidence partially conflicts with these results, determining that a P. aeruginosa oprF mutant produces lower levels of PQS (67). Our study likely contradicts this study due to the fact that different quantification methods were used: Fito-Boncompte et al (67) used an LC/MS method (68) to quantify PQS, and this study used TLC.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…4B and C). Recent evidence partially conflicts with these results, determining that a P. aeruginosa oprF mutant produces lower levels of PQS (67). Our study likely contradicts this study due to the fact that different quantification methods were used: Fito-Boncompte et al (67) used an LC/MS method (68) to quantify PQS, and this study used TLC.…”
Section: Resultscontrasting
confidence: 54%
“…Recent evidence partially conflicts with these results, determining that a P. aeruginosa oprF mutant produces lower levels of PQS (67). Our study likely contradicts this study due to the fact that different quantification methods were used: Fito-Boncompte et al (67) used an LC/MS method (68) to quantify PQS, and this study used TLC. In contrast to Fito-Boncompte et al, we and others have found that in the absence of a chelator in the mobile phase, PQS is difficult to quantify using liquid chromatography (66, 69) due to poor peak resolution; thus, TLC provides a more quantifiable approach.…”
Section: Resultscontrasting
confidence: 54%
“…OprF is an outer membrane porin and an important virulence factor. 32 OprH provides stability to the outer membrane through interaction with lipopolysaccharide, 33 while OprG has potential porin function. 34 A literature search did not reveal any vaccine studies on OprH or OprG.…”
Section: Mucosal and Systemic Antibody Responses To Potential Pseudommentioning
confidence: 99%
“…OprF binds IFN-g, leading to stimulation of the quorum-sensing network (40). Oprf deletion mutants define a role of OprF in virulence, partly through modulation of quorum-sensing (41). In light of this evidence for OprF immunogenicity and hyperexpression during biofilm formation, it might be predicted that patients undergoing such infection would show enhanced OprF adaptive immunity: it has previously been shown by others and confirmed by us that chronic infection is associated with raised antibody titers (6,37).…”
Section: Original Article Discussionmentioning
confidence: 96%